The Greely Arctic expedition : as fully narrated by Lieut. Greely, U.S.A., and other survivors - Schley, Winifred Scott, 1839-1911; Barclay, George L. (George Lippard), 1849 or 50-1886; Greely, A. W. (Adolphus Washington), 1844-1935 (Philadelphia : Barclay & Co., 1884)
Mode of access: Internet.